The Rise of Political Influencers—Perspectives on a Trend Towards Meaningful Content - Riedl, Magdalena; Schwemmer, Carsten; Ziewiecki, Sandra; Ross, Lisa M. (Frontiers in Communication, 2021)
Despite an increasing information overflow in the era of digital communication, influencers manage to draw the attention of their followers with an authentic and casual appearance. Reaching large audiences on social media, they can be considered as digital opinion leaders. In the past, they predominantly appeared as experts for topics like fashion, sports, or gaming and used their status to cooperate with brands for marketing purposes. However, since recently influencers also turn towards more meaningful and political content. In this article, we share our perspective on the rise of political influencers using examples of sustainability and related topics covered on Instagram. By applying a qualitative observational approach, we illustrate how influencers make political communication look easy, while at the same time seamlessly integrating product promotions in their social media feeds. In this context, we discuss positive aspects of political influencers like contributions to education and political engagement, but also negative aspects such as the potential amplification of radical political ideology or conspiracy theories. We conclude by highlighting political influencers as an important research topic for conceptual and empirical studies in the future.